Modeling and assessment of dental health behavior among elementary school students using the Health Belief Model (HBM) with the OHBQAHBM instrument: a cross-sectional study - Florensia, Maria; Vita, Helena; Putri, Tresna; Evan, Kennard; Abigayl, Ivana (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRAKIntroduction: Dental health behavior is an important aspect of elementary school students’ well-being, especially for those in grade 6 who are in the phase of permanent tooth eruption. The Health Belief Model (HBM) is one of the health behavior theories commonly used to explain and predict individual health behaviors, including oral health behavior in children. This analytical cross-sectional study aimed to analyze the dental health behavior of 6th-grade students at SD MIN 3 Banjar using the HBM approach. Methods: This study used an analytical cross-sectional design. Data were collected using the Oral Health Behavior Questionnaire for Adolescents Based on the Health Belief Model (OHBQAHBM) instrument, with total sampling applied to the entire population. The data obtained from the questionnaires were analyzed by calculating percentage scores. Results: The total number of subjects in this study were 28 students. The results showed that 39.3% of respondents had a neutral attitude toward perceived susceptibility, 42% were neutral regarding perceived benefits, and 38% did not experience significant barriers. Regarding cues to action, 34.5% lacked triggers for dental health behavior. Perceived severity showed an even distribution (22.4%) between those who considered it serious and somewhat serious. Meanwhile, 25.7% expressed low confidence in their ability to maintain dental health (self-efficacy). Conclusion: Students who demonstrated neutral perceptions of susceptibility and benefits and reported few barriers also showed limited cues to action and self-confidence. Interventions are needed to enhance students’ awareness and self-efficacy in maintaining good oral health.KEY WORDS: health Belief Model, behaviour, dental health, students, elementary school Pemodelan dan pengujian perilaku kesehatan gigi pada siswa sekolah dasar dengan pendekatan Health Belief Model menggunakan instrumen OHBQAHBM: Studi cross-sectionalABSTRACT Pendahuluan: Perilaku kesehatan gigi merupakan aspek penting bagi siswa sekolah dasar, terutama kelas 6 yang berada dalam masa pertumbuhan gigi permanen. Health Belief Model (HBM) merupakan salah satu teori perilaku kesehatan yang efektif dalam menjelaskan dan memprediksi perilaku kesehatan individu, termasuk perilaku kesehatan gigi pada anak. Penelitian analitik cross-sectional ini bertujuan menganalisis perilaku kesehatan gigi pada siswa sekolah dasar menggunakan pendekatan HBM. Metode: Jenis penelitian menggunakan analitik cross-sectional. Pengumpulan data menggunakan instrumen Oral Health Behavior Questionnaire for Adolescents Based on Health Belief Model (OHBQAHBM) dengan pengambilan sampel metode total sampling dari populasi. Data yang telah didapatkan dari hasil kuesioner selanjutnya dilakukan perhitungan skor persentase  Hasil: Total subjek pada penelitian ini adalah 28 siswa dengan hasil penelitian menunjukkan 39,3% responden bersikap netral terhadap perceived susceptibility, 42% netral terhadap perceived benefits, dan 38% tidak mengalami barriers signifikan. Pada cues to action, 34,5% tidak memiliki pemicu perilaku kesehatan gigi. Perceived severity menunjukkan distribusi merata (22,4%) antara yang menganggap serius dan agak serius. Sementara 25,7% menyatakan kurang yakin dengan kemampuan menjaga kesehatan gigi (self-efficacy). Simpulan: Siswa yang menunjukkan persepsi netral tentang kerentanan dan manfaat serta melaporkan sedikit hambatan, mereka memiliki keterbatasan dalam isyarat bertindak dan keyakinan diri. Diperlukan intervensi untuk meningkatkan kesadaran dan kepercayaan diri siswa dalam menjaga kesehatan gigi.KATA KUNCI: health belief model, perilaku, kesehatan gigi, siswa, sekolah dasar